A community based study of neonatal mortality in Aligarh by using verbal autopsy - Chauhan, Ambren; Shah, M. Salman; Khalique, Najam; Eram, Uzma (International Journal Of Community Medicine And Public Health, 2018)
Background:Neonatal mortality rate is regarded as an important and sensitive indicator of the health status of a community. Children face the highest risk of dying in their first month of life. The present study was aimed to 1) determine the prevalence of neonatal mortality rate 2) identify socio-biological factors in relation to neonatal mortality.3) determine the causes of neonatal mortality. Methods:A community based cross sectional study was conducted in the field practice areas of Department of Community Medicine, AMU, Aligarh. All the live births and all neonatal deaths were taken for one year from June 2016 to May 2017. A standard Verbal autopsy questionnaire (WHO 2012) was used as a study tool. Results:The prevalence of neonatal mortality rate was38.2/1000 live births. The early neonatal mortality rate was 28.3/1000 live births and late neonatal mortality rate was 9.9/1000 live births. The associated socio –biological factors were gender [OR-2.381, 95% CI-1.037-5.468], birth order [OR-4.090, 95% CI-1.119-14.946] and gestational age [OR-12.62, 95% CI-3.26-48.82]. The leading causes of deaths among newborns were preterm births (22.2%), birth asphyxia (22.2%), other causes (19%), ARI (14.3%), congenital anomalies (14.3%) and diarrhoeaandneonatal sepsis accounted for (4.8%) each. Conclusions: The neonatal mortality rate assessed by verbal autopsy is higher than nationally reported. Most of the deaths were in early neonatal period. There is a need for programs encouraging the use of antenatal care, encouraging institutional deliveries and care of LBW neonates; as well as implementation of community-based newborn survival strategies.